PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN DENGAN RISIKO KREDIT SEBAGAI VARIABEL INTERVENING - Nindya Permatasania, (2023)
This research is a quantitative study that aims to determine the influence of the application of good corporate governance in terms of self-assessment of banking financial performance with credit risk as an intermediary variable. This study used IDX-listed banking as a population. With the purposive sampling method, as many as 40 conventional banks were obtained as samples in this study. The data used are secondary data obtained from annual reports, financial statements, and self-assessment reports of each bank. Hypothesis testing in this study used multiple linear regression analysis with SmartPLS version 3.2.9 software with a significance level of 5% (0.05). Results from the test obtained 1) good corporate governance has a positive influence on financial performance. 2) good corporate governance has a negative influence on credit risk. 3) credit risk has a negative influence on financial performance. 4) good corporate governance has an influence on financial performance through credit risk as an intervening variable.